THE PROFILE OF THE ROMANIAN ACCOUNTANT - Cristina Elena BIGIOI (Challenges of the Knowledge Society)
Tax and accounting rules are required by law for each company. The accountant has an important role in the life of an enterprise, contributing greatly to the business success. The study aims to identify the benefits, requirements and features specified to apply for a job as accountant. The methodological approach is empirical one. The study take into account the job offers mentioned in December 2016 under one of the most popular Romanian jobs sites.